Peran Lipopolisakarida Helicobacter pylori terhadap Aktivitas Neutrofil pada Penderita Infark Miokard Akut melalui Degradasi Kolagen Tipe IV - Djanggan Sargowo; I Ketut Gede Muliartha; Mudyawati Kamaruddin (The Indonesian Heart Association, 2007)
Matrix metalloproteases (MMPs) are proteolytic enzymes that play a criti-cal role in decreasing the stability of atherosclerotic plaque causing Acute Myocardial Infarction (AMI). In this process, degradation of type IV col-lagen as an important component of endothelial membrane is thought to be important. Several microorganisms and their products including Li-popolysaccharide (LPS) have been suggested to be able to activate MMPs.The aim of this study is to investigate the role of Helicobacter pyloriLPS in type IV collagen degradation (in vitro). We used two stages in this study: MMP production stage and degradation of type IV collagen. MMP derived from the neutrophils of AMI and non-AMI patients that had been stimulated with LPS of Helicobacter pyloriwere used to digest type IV collagen. Analysis of type IV collagen degradation was performed with SDS-PAGE and Western blot.This study showed MMP isolated from neutrophil of AMI patients is an active MMP-9 at Molecular weight of 72 kDa. It can degrade type IV col-lagen at MW 78.6 kDa, 60 kDa, 50 kDa, 47.8 kDa and 43.8 kDa. Whereas MMP isolated from neutrophil of non-AMI have MW of 91.2 kDa and can only degrade collagen IVat merely 60 kDa.In conclusion, Helicobacter pyloriLPS is able to induce neutrophil of AMI patients to produce an active MMP-9 at MW 72 kDa and the enzyme may play strategic role in the degradation of type IV collagen.